THE PRODUCTION OF PEDADA FRUIT JAM (SUBSTITUTION OF PEDADA FRUIT) (Sonneratia caseolaris)) WITH HAWAIIAN PAPAYA (Carica papaya L.) - Isye Selvianti; Marisa Nopriyanti; Emy Arahman; Dwi Yoga (Jurnal Pengembangan Agroindustri Terapan, 2023)
The purpose of this study is to find out how mangrove apple jam is made (mangrove apple (Sonneratia caseolaris) substituted with Hawaiian papaya (Carica papayaL.)). Mangrove apple jam is made through several processes which includes the preparation of ingredients, fruit smoothing, heating or cooking, and the addition of sugar that is 40% of the overall weight of the ingredients. The cooking process of the jam takes 15 minutes in 105°C temperature while being constantly stirred until it becomes thick. The method used for this study is chemical testing by analyzing the water content, ash content, the total acidity and pH. The calculation results show that the mangrove apple jam, mangrove apple (Sonneratia caseolaris) being substituted with Hawaiian papaya (Carica papaya L.) given the 50%:50% treatment was the best treatment possible. The jam had 12,47% water content, 16,89% ash content, 9,5% acidity, and pH 4.